The Effect of Pregnancy Exercises on Low Back Pain in Pregnant Women - Irni Setyawati; Kusniyati Utami; Hardaniyati; Dian Soekmawaty Riezqy Ariendha (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Low back pain is common in pregnancy with varying reported incidences. Low back pain is back pain that occurs in the lumbosacral region. In general, back pain that occurs in pregnant women is influenced by several factors, namely changes in body posture during pregnancy, low back pain usually increases with parity. The risk of back pain in pregnancy is increased in women who have previously had back pain and are overweight. National guidelines recommend that healthy pregnant women should do light physical exercise every day. Most women reduce physical activity during pregnancy and only a few studies have found that pregnant women are physically active during pregnancy.The purpose of this study was to determine the effect of Pregnancy Exercises on Back Pain in Pregnant Women. The method in this study is a literature review, which tries to explore how the effect. The results in this study indicate that the results of 8 previous studies indicate that there is a significant effect of Pregnancy Exercises on Back Pain in Pregnant Women. The conclusion in this study is that of Pregnancy Exercises can reduce Back Pain in Pregnant Women. Pregnancy exercise or exercise can provide benefits to maintain and improve the physical health of pregnant women, improve blood circulation, reduce complaints of cramps or aches, and prepare for breathing, muscle and pelvic activity to face the labor process. Pregnancy exercise has very important benefits for pregnant women.